(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It has been argued that gender hasan impact on food choice and doing behaviour decisions. The majority of femalesare responsible for the weekly food shop hence this should influence theirinteraction decision, especially when the female is interaction on behalf ofthe family unit . Women are reported to have higher intakes of fruits andvegetables, higher in takes of dietary fibre and lower intakes of fat thanmales. Wardle, Haase, Steptoe, Nillapun, Jonwutiwes, and Bellisle havesupported this research, stated that women were more likely to avoid high fatfoods. More likely to be dieting and placed a greater importance on healthyfood. Age has an influence on doing behaviour in the shape that different agegroups have different needs. In comparison to younger people, the elderly Humaneat lesser and make different food choices. A series of focus groupsaccomplished by chambers, has showndifferences with food choices decisions between age groups. They further statedthat 60 plus age group to be more likely to make food choices based on healthconsideratios, on the other hand, those 18-30 are more likely to base theirdecisions on their knowledge of the food, how it is prepared as well as howmuch it costs and the time constraints associated with it.It can be a matter ofdebate that both family and household influences affect Social doing behaviour.Families include of individuals related by blood, marriage, adoption andemotional commitment. However a household is different to a family, in that itcan be defined as a person or group of co-habiting persons who jointly managetime and money budgets. A spending priorities can get affected by a familystructure in the sense that a mother will be influenced to some extent by whather husband and children like to eat, and may do things for them she would notconsume for herself.